GegenRomantik (De Gruyter, 2024)
The volume Against/Romanticism deals with Romanticism as a source of controversy. In the name of what ideas and behaviors was Romanticism criticized in the natural sciences and aesthetics, and in political contexts? Romanticism as well as its critics and opponents responded to some of the fundamental issues of modernity. The controversy sounding Romanticism can therefore be used to draw out the principle aporias of modern thought.